Peningkatan Prestasi Belajar Ips Dengan Model Pembelajaran Example Non Example Pada Siswa Kelas V SDN Bontoramba - Asriani Asriani; Ince Prabu Setiawan; Nur Afni; Erwin Nurdiansyah; Nasaruddin Nasaruddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Based on the background of the problem and the identification of the problem that has been described above are: Can the example non example learning model improve social studies learning achievement for class V SDN Bontoramba. This study aims to improve social studies learning achievement with an example non-example learning model for fifth grade students at SDN Bontoramba. Based on the results of the research that has been done, it is concluded that learning through Example and Non-Example learning models can improve learning achievement in Social Studies learning material on the meaning of historical heritage with Hindu-Buddhist and Islamic patterns in Indonesia. By using the Example and Non-Example learning models, it shows that in the first cycle the results of observations of student learning activities are in the sufficient category, which means that they have not yet reached the indicators of learning implementation. Whereas in cycle II the results of observations of student learning activities were in the good category so that they had reached the indicators of learning implementation. In the first cycle of learning test results there were still 50% of students who did not complete, so they had not reached the specified classical completeness and had not reached the Maximum Completeness Criteria (KKM). Whereas in cycle II the results of student learning tests were 100% of students who had passed so that they had achieved the specified classical completeness and had reached the Maximum Completeness Criteria (KKM) so that this research was considered successful.